Historical and Theoretical Approach To the Problem of Genre in Modern Russian Literature Studies - Osipova, Agata Viktorovna (RA Journal of Applied Research, 2021)
The article is devoted to the study of the peculiarities of the genre in Russian literary criticism. A brief overview of the research opinions of prominent scientists on the problem of the genre system and its evolution is given. An attempt is made to investigate the transformation of the genre of the modern story. Particular attention is paid to the change in the genre nature of the story as a result of the artistic interpretation of reality by contemporary Russian postmodernists.